Design, Construction and Performance Evaluation of Chicken De-Feathering Machine - Abubakar, M.; Zakariyah, A.; Usman, A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
The demand for poultry meat world-wide has imposed great responsibility on poultry processing industry, and especially in de-feathering operation which is usually achieved manually in Nigeria. Being a core stage of poultry processing, de-feathering when carried out manually attracts low production rate (the number of birds produced per hour), high time consumption and labour intensity. This study was focused on design, construction and performance evaluation of chicken de-feathering machine using locally available materials. The design was based on market weight of chicken. The selected materials used to fabricate the machine were trimmed tyre rubber, sheet metals, angle iron and shaft. The rubber cross section was 20 mm×20mm and were arranged both on the shaft length (50mm, 70mm, 90mm, 110mm, 130mm and150mm in length) and at the wall of the bottom cone (80mm length). The height of the machine was 1400mm and 500mm×500mm square area. The performance evaluation result showed that chicken variety had effect on the de-feathering efficiency, throughput capacity and energy consumption of the machine. Scalding time and scalding temperature did not significantly affect throughput capacity and energy consumption but scalding temperature had significant effect on de-feathering efficiency. Maximum mean throughput capacity of 1034 chickens per hour was obtained at 96 % de-feathering efficiency.